Leaf-cutter ant parasitoids: current knowledge - Folgarait, Patricia Julia (2013)
This review updates and summarizes the current knowledge about the interaction of leaf-cutter ants and their parasitoids by providing comparable data for Acromyrmex and Atta ants. First, an overview of the relevant aspects of the biology and taxonomy of leaf cutters and of their parasitoids is provided. Second, I show the peculiarities of the parasitoids attacking behaviors towards their host as well as the responses or ant defenses against the phorids exhibited by their hosts. Third, I discuss relevant aspects of the interactions between hosts and parasitoids. Finally, the review ends demonstrating why these phorids could be promising biological control agents of leaf-cutter pests and suggests priority lines of research for the future.